Single nucleotide polymorphism screening and bioinformatics analysis of myostatin gene in Jingning chicken - ZHANG Li; LIU Lixia; DAI Hongwei; CHEN Hong; WANG Rui; YUE Binghui (浙江大学学报. 农业与生命科学版)
In order to screen out the individuals of myostatin (MSTN) gene mutation, and breed fine poultry breeds with higher meat yield through a number of generations in Jingning chicken population, the fifth generation of Jingning chicken was selected as experimental objects to construct DNA pools, and the MSTN gene encoding sequence of Jingning chicken was obtained through segment amplification method, and the single nucleotide polymorphism (SNP) screening and bioinformatics analysis were carried out. The results showed that the coding sequence (CDS) region of MSTN gene in Jingning chicken was 1 128 bp long, encoding 375 amino acids, and the protein encoded by MSTN gene was hydrophilic protein. Four SNPs were found in CDS region including exon1-c.60G>A, exon1-c.195C>G, exon1-c.234G>A, exon3-c.966G>T, which were all synonymous mutations. The change of mRNA, secondary structure and free energy after nucleotide mutation led to the change of its structural stability. The main components of the protein secondary structure and tertiary structure were random coil, and the extended strand, α-helix and β-turn were scattered throughout the protein structure. The above result indicates that the MSTN gene of Jingning chicken has high mutagenicity, which provides molecular basis for marker-assisted selection of growth traits in Jingning chicken.